Modern political analysis - Bruce, Stinebrickner (Prentice-Hall of India Pvt.Ltd Pakistan, 2004)
A thoroughly revised new edition, this compact text provides an analysis and description of democracy, political behavior, political evaluation, policy making and comparative political systems. The treatment of influence and the nature of politics too is substantially revised and rearranged in a manner to enhance the grasp of the topics by students. The revision takes into account the changes in the global political scenario such as the September 11, 2001 attacks, the demise of the Soviet Union and the number of sovereign states on this planet etc. and concludes with a new chapter, "What Good Is Modern Political Analysis".